Redox homeostasis, oxidative stress and antioxidant system in health and disease: the possibility of modulation by antioxidants - Kotur-Stevuljević, Jelena; Savić, Jelena; Simić, Milena; Ivanišević, Jasmina (Archives of Pharmacy, 2023)
Redox imbalance occurs when the factors of oxidative stress, known as prooxidants, outweigh the mechanisms of antioxidant protection. In a healthy state, homeostatic mechanisms ensure the balanced production of free radicals and a complete series of antioxidants responsible for their safe removal. The generation of free radicals is a part of physiological processes in a healthy organism, some of which act as specific signaling molecules, and their presence and activity are necessary in these processes. In various diseases such as cancer, cardiovascular disease, diabetes, autoimmune diseases, rheumatic diseases, systemic lupus, and skin diseases, the generation of free radicals overwhelms the protective mechanisms, leading to the development of "oxidative stress" that damages cells and tissues. To prevent the harmful effects of free radicals within cells, there exists a system of enzymatic antioxidant protection composed of superoxide dismutase (SOD), glutathione peroxidase (GSHPx), glutathione reductase (GR), glutaredoxin, reduced/oxidized glutathione (GSH/GSSG), and thioredoxin (TRX). The examples of non-enzymatic antioxidants are: antioxidant vitamins such as A, C and E, dihydrolypoic acid, metallothioneins, ceruloplasmin, coenzyme Q 10, urea, creatinine, etc. Redox balance is influenced by the circadian rhythm and external factors that constitute the "exposome", including dietary habits and lifestyle. Antioxidant supplementation has become increasingly popular for maintaining optimal body function. However, it is important to note that some antioxidants can exhibit prooxidant activity, emphasizing the need for controlled use. The relationship between the redox status of the body and the action of antioxidants enables the development of multidisciplinary research that connects biochemistry, molecular biology, nutritional science, natural product chemistry, and clinical practice.
Keywords: antioxidants; prooxidants; free radicals; enzymatica antioxidant protection